2019
DOI: 10.4467/2353737xct.19.102.10884
|View full text |Cite
|
Sign up to set email alerts
|

A housing market analysis for the city of Krakow

Abstract: This article presents the results of a housing market analysis for the city of Krakow. The market study was performed in May 2019 using the online survey method on a group of 104 persons who were currently searching for an apartment. Based on initial studies, the authors analysed the opinions of potential customers, identified the apartments enjoying the highest demand, described the preferences of potential buyers and the criteria that encourage buying real estate to the greatest extent. Based on the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The results showed that house prices, income, and credit accessibility significantly influence housing investors' purchase decisions in a positive direction. Adamkiewicz & Radziszewska-Zielina (2019) conducted an online survey on a group of 104 persons who were currently searching for an apartment. Based on the outcomes, they concluded that the perceived need for persons to have their apartment is the most common reason for purchasing a house.…”
Section: Theoretical Basicmentioning
confidence: 99%
“…The results showed that house prices, income, and credit accessibility significantly influence housing investors' purchase decisions in a positive direction. Adamkiewicz & Radziszewska-Zielina (2019) conducted an online survey on a group of 104 persons who were currently searching for an apartment. Based on the outcomes, they concluded that the perceived need for persons to have their apartment is the most common reason for purchasing a house.…”
Section: Theoretical Basicmentioning
confidence: 99%